Developing English Materials for Students with Visual Impairment at Language Development Center (P2B) State Islamic University (UIN) Sunan Kalijaga - Dharmasanti Rawidya Putri (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
AbstractThe research starts from the necessity of the visual impairment students to have their own and specific media to learn due to their disability condition. The research is conducted in State Islamic University Sunan Kalijaga Yogyakarta as one of the inclusive university in Indonesia. The research involves four visual impairment students who learn English subject together with another non-visual impairment student in Class P academic year 2014/2015. The development of the English materials involves the conduct of need analysis to know the need of the topic of English subject. This study belongs to Research and Development (R&D). in which educational R & D is a process used to develop and validate educational products. The result of the study is the need analysis itself and the development of the English material based on the need analysis. Keywords: Development of Materials, Need Analysis, and Inclusive Education.AbstrakPenelitian ini berawal dari kebutuhan mahasiswa tuna netra tersebut untuk memiliki media pembelajaran Bahasa Inggris sendiri yang sesuai dengan kondisi disabilitas mereka. Penelitian ini dilakukan di Universitas Islam Negeri Sunan Kalijaga Yogyakarta yang merupakan universitas inklusi di Yogyakarta. Penelitiuan ini melibatkan empat mahasiswa tuna netra yang belajar Bahasa Inggris bersama-sama dengan mahasiswa non disabilitas di Kelas P tahun ajaran 2014/2015. Pengembangan modul Bahasa Inggris ini menggunakan analisis kebutuhan untuk mengetahui topic atau tema apa saja yang dibutuhkan mahasiswa tuna netra dalam pembelajaran Bahasa Inggris. Penelitian ini termasuk dalam bidang Pengembangan dan Penelitian untuk mengembangkan dan memvalidasi sebuah produk pendidikan. Hasil penelitian berupa analisis kebutuhan dan modul pembelajaran Bahasa Inggris untuk mahasiswa tuna netra di Universitas Islam Negeri Sunan Kalijaga Yogyakarta.Kata Kunci: Pengembangan Modul, Analisis Kebutuhan, Pendidikan Inklusi.